Cavity ring down spectroscopy of 17O enriched water vapor near 1.73 µm. (January 2019) - Mikhailenko, S.N.; Mondelain, D.; Karlovets, E.V.; Kassi, S.; Campargue, A.
Highlights: The CRDS spectrum of 17 O enriched water vapour is recorded between 5693 to 5850 cm −1 . The sensitivity of the recordings ( α min ) is better than 10 −10  cm −1 . 1132 water lines were assigned to 1220 transitions of five water isotopologues. 104 new energy levels were derived mostly for H2 17 O, H2 18 O and HD 17 O. Some disagreements with the HITRAN2016 line list of water vapor are discussed. Abstract: The room temperature absorption spectrum of water vapour highly enriched in 17 O is recorded by cavity ring down spectroscopy (CRDS) near 1.73 µm. Two series of recordings were performed with pressure values of about 0.12 and 8.5 Torr from 5693 to 5850 cm −1 . The noise equivalent absorption ( α min ) of the spectra is better than 10 −10  cm −1 allowing for the measurements of water lines with intensity down to 10 −29  cm/molecule. A total of 1132 lines were assigned to 1220 transitions of five water isotopologues (H2 16 O, H2 17 O, H2 18 O, HD 16 O, and HD 17 O). Their intensities span near five orders of magnitude from 10 −29 to 10 −24  cm/molecule at 296 K. The assignments were performed using known experimental energy levels as well as calculated line lists based on the results of Schwenke and Partridge. Most of the new results concern the H2 17 O isotopologue: 483 transitions were measured while only the 27 strongest were previously known. Overall 104 levels were newly determined for H2 17 O (64 levels), H2 18 O (16), HD 17 O (23) and HD 16 O (1) and a few additional levels were corrected compared to the literature. The obtained results are compared to the water line list in the HITRAN2016 database, to the ExoMol energy levels and to the empirical energy levels recommended by an IUPAC task group.